Dinamika Penggunaan Sistem Rujukan Terintegrasi (SISRUTE) di Puskesmas Kota Tangerang Selatan - Elyarna Shania Wahyudi; Septo Pawelas Arso; Putri Asmita Wigati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
South Tangerang City is a city that has used the Integrated Referral System (SISRUTE) in 29 Health Centers and 30 hospitals. However, the use of SISRUTE in the referral process at the South Tangerang City Health Center had decrease in 2019-2021. Meanwhile, in 2022 the use of SISRUTE in the referral process began to increase. The Puskesmas officer stated that they still found several obtacles in the use of SISRUTE such as the understanding of officers, facilitating conditions, the quality of the SISRUTE application and the absence of SOP’s related to the use of SISRUTE in the referral process. The purpose of this study was to related factors to the use of SISRUTE in South Tangerang City Health Centers. This research is quantitative study with cross sectional approach that which was carried out on February-August 2022 at South Tangerang City Health Centers. There are dependent variables (performance expectancy, effort expectancy, social influence, dan facilitating conditions) and independent variable (use behavior) used in this research. The research sample was 58 people from 15 South Tangerang City Health Centers with kuota sampling technique. The results obtained are the most (62.1%) respondents use SISRUTE well. In conclusion, performance expectancy (p-value = 0.004), effort expectancy (p-value = 0.005), and facilitating conditions (p-value = 0.005) are related to use of SISRUTE. Meanwhile, social influence is not related to use of SISRUTE (p-value = 0.098).